2014
DOI: 10.1038/sc.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

50 years follow-up on plasma creatinine levels after spinal cord injury

Abstract: Study design: Retrospective chart review. Objectives: To investigate the role of plasma creatinine (p-creatinine) in monitoring renal deterioration in patients up to 50 years after spinal cord injury (SCI). Setting: The Clinic for Spinal Cord Injuries, Rigshospitalet, Denmark. Methods: A total of 119 patients with a traumatic SCI during the years were included in the study. P-creatinine measurements, results from renography and glomerular filtration rate (GFR) measured with 51 Cr-EDTA clearance were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In addition, although previous experimental models have shown that the expression of sclerostin is highly up regulated by unloading and that mice lacking sclerostin expression are insensitive to unloading bone loss, it is interesting to note that treatment with sclerostin antibodies in mice submitted to unloading could not fully counteract the effects of unloading in bone . Conversely, the effects of Dkk‐1 antibodies on bone mass in the same rat model under unloading was associated with a marked increase in bone mass in this condition suggesting an important role of Dkk‐1 in mediating bone loss in unloading conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, although previous experimental models have shown that the expression of sclerostin is highly up regulated by unloading and that mice lacking sclerostin expression are insensitive to unloading bone loss, it is interesting to note that treatment with sclerostin antibodies in mice submitted to unloading could not fully counteract the effects of unloading in bone . Conversely, the effects of Dkk‐1 antibodies on bone mass in the same rat model under unloading was associated with a marked increase in bone mass in this condition suggesting an important role of Dkk‐1 in mediating bone loss in unloading conditions.…”
Section: Discussionmentioning
confidence: 93%
“…As expected, phosphate serum levels were increased and creatinine values were decreased at baseline in SCI patients, being two well known features attributed to the loss of phosphorus from bones and muscle and the diffuse muscle atrophy that occurs after SCI. (1,28) At baseline (time-since-injury of 100 AE 33 days) SCI patients showed a marked increase of $ 3-fold in bone turnover markers (PINP and sCTx) compared to controls (Table 1), which remained significantly increased at 6 months of follow-up; at 12 months both markers decreased, and no significant differences were observed compared to the control group ( Figure 2). Conversely, bone ALP did not show significant differences compared to controls at either baseline or during follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…There is no doubt about that determination of endogenous creatinine serum level is the most widely used indirect measure of glomerular filtration rate as it is convenient and cheap, although is of low sensitivity even to substantial renal function impairment in addition to problematic interpretation [9], so that serum creatinine that falls in the so-called "normal" value in a young, healthy individual may in an elderly patient indicate a significant reduction in GFR due to old age or disease state [10]. Long time follow-up on ability of plasma creatinine value in individuals, who have sustained spinal cord injury has already confirmed that plasma creatinine is a poor detector of early stage renal function deterioration [11] Meanwhile, progressive renal impairment after spinal cord injury is well documented [12] at least for acute stage of the injury and may be associated with many changes that can affect disposition of drugs such as aminoglycosides. Therefore, dosing of aminoglycosides in such patients can be challenging due to changes in some important pharmacokinetic parameters such as volume of distribution, clearance, and half-life of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…On multivariate analysis, age was also one of the factors related to overestimation of renal function using eGFRcre. Some reports describe that serum Cre decreases over time in SCI patients, despite an increasing risk of developing renal insufficiency [23]. Extensive loss of muscle mass with increasing age in SCI patients is thought to be the biggest reason for the decrease in serum Cre.…”
Section: Discussionmentioning
confidence: 99%